Winnie-The-Pooh : The Complete Collection of Stories and Poems - Milne, A. A. 1882-1956; With Illustrations by Shepard, E. H. (London Methuen Books, 1994)
This gift edition contains all four of A.A. Milne's classic children's books of verse and stories about Christopher Robin and Winnie-the-Pooh, accompanied by E.H. Shepard's original drawings and illustrations
Include Picture
Keywords: Toys -- Winnie-the-Pooh (Fictitious character) -- Teddy bears